(3eMGVQGJ hJeGQjf aj ebjGS GdJMdjd GdeGdj (B: s (3eWHhYI YdejI ebOeI dWdHI GdSfI GdKGdKI djSGfS eMGSHI h eGdjI (B/ s - (3SGjM, aQjOs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3eONd ddJMdjd GdeGdj, JMdjd GdgjcdI GdeGdjI h GdfTGW, JMdjd GdeQOhOjI h GdQGaYI GdeGdjI, JMdjd GdJOabGJ GdeGdjI(B.s
(3eQGLY U(B.108s
Keywords: (3GdGehGds; (3GdJMdjd GdeGdjs